Effectiveness of Morinda citrifolia juice as an intracanal irrigant in deciduous molars: An in vivo study - Manisha Chandwani; Rakesh Mittal; Shweta Chandak; Jitesh Pimpale (Wolters Kluwer Medknow Publications, 2017)
Background: The purpose of this study was to evaluate the microbial reduction in deciduous molars using Morinda citrifolia juice (MCJ) as irrigating solution. Materials and Methods: This was a randomized comparative study including 60 deciduous molars chosen among the patients belonging to the age group of 6-9 years based on the inclusion or exclusion criteria. The selected teeth were divided randomly into two groups based on irrigation solution used, that was, Group I (1% NaOCl) and Group II (MCJ). The microbial samples were collected both pre- and post-irrigation and were transferred for microbial assay. Paired t-test was used for intragroup analysis of pre- and post-operative mean reduction of bacterial colony forming unit (CFU)/ml, whereas Independent t-test was used to assess the intergroup, pre- and post-operative mean reduction of bacterial CFU/ml. Results: In the intragroup comparison, both of the groups showed statistically significant (P < 0.001) reduction in the mean CFU/ml; however, it did not show statistically significant reduction when intergroup comparison was carried out between the two groups. Both the study materials had clinically revealed decrease in the microbial count postirrigation. Conclusion: Both the irrigants, 1% NaOCl and MCJ, were significantly effective in the reduction of mean CFUs/ml postoperatively. The results of this study have confirmed the antibacterial effectiveness of MCJ in the root canals of deciduous teeth. Considering the low toxicity and antibacterial effectiveness of MCJ, it can be advocated as a root canal irrigant in endodontic treatment of primary teeth.